PENGARUH PENERAPAN MODEL PEMBELAJARAN CROSSWORD PUZZLE TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN PKN KELAS III UPT SPF SD INPRES MINASAUPA I - Nurasharaeni Mardania Darmawan; Abdul Azis; Rismawati (STKIP Subang, 2025)
This study aims to determine the effect of the Crossword Puzzle learning model on student learning outcomes in Civics Education (PKN) subjects at Grade III UPT SPF SD Inpres Minasaupa I. The research employed a quantitative method with a one- group pretest-posttest pre-experimental design. The sample consisted of 26 students from class III A. Data were collected through pretest and posttest multiple- choice questions, observation sheets, and documentation. The analysis showed an increase in the average score from 46.73 (pretest) to 89.23 (posttest). A paired sample t-test resulted in a significance value of < 0.001, indicating a significant difference before and after the implementation of the Crossword Puzzle model. Thus, this model has a significant impact on improving student learning outcomes, enhancing motivation, and encouraging active participation in learning activities.